Dynamika zmian budowy, struktury i składu gatunkowego drzewostanów o charakterze pierwotnym na wybranych powierzchniach w Pienińskim Parku Narodowym - Jaworski, Andrzej; Jakubowska, Dorota (Leśne Prace Badawcze, 2011)
The aim of this study was to investigate changes in species composition, structure, developmental stages and phases that have occurred in four stands of Pieniny National Park within the last 33 years (1974-2007). The standing volume of growing stock was calculated with the use of a height curve determined on the basis of measurements in 2007. Walusiówka stand was in a growth phase in 2007, comprising an opening phase with ongoing recovery phase, and its growing stock volume during the studied period decreased slightly from 687 to 681 m 3 •ha –1 . Przełęcz Sosnów Stand structure in 1974 was in the initial phase of the optimal stage. Between the years 1974-2007 as a result of the die -back, fires and disruption caused by the wind, the growing stock volume decreased from 691 to 549 m 3 •ha –1 , this trend appears to represent a degradation process. In this stand the natural developmental cycle of the primary forest was disturbed, as described by Korpel. Instead of reaching the optimal stage, the growth phase and storey building phase were attained. During the entire study period the Ociemne stand remained in a growth phase, the phase of selection construction and renewal, and its growing stock volume increased from 544 to 612 m 3 •ha –1 . The Facimiech stand was at its optimal stage in 1974 and by 2007 reached the optimum stage in the aging and renewal phases; its a growing stock volume increased from 658 to 730 m 3 •ha –1 during this time. Between the years 1974-2007 there was a decline in the proportion of fir stand volume in three of the stands: in Walusiówka from 44 to 31%, in Przełęcz Sosnów from 60 to 33%, and in Ociemne from 40 to 26%. In the Famiciech stand the proportion of fir (ab. 99%) did not change significantly though beech increased to (0.4%). The small share of fir and beech in the undergrowth of stands composed of these species suggests that beech share will increase while fir share will decrease. Although various types of disturbance remain the stands are stable, well-balanced and nowhere exhibit widespread decay. In the examined sites, no simplification of the vertical structure has taken place; with the proportion of fir decreasing as it is replaced by beech. In the stands representing good habitat for fir, breeding programmes must be designed that allow it to coexist with beech in lower subalpine forest stands.